Implications of higher inflation and interest rates for macroprudential policy stance - Hannah S. Hempell; Fatima Silva; Valerio Scalone; Tamás Borkó; Wanda Cornacchia; Domenica Di Virgilio; Aurélien Espic; Salomón Garcia; Marcel Heires; Luis Herrera; Samu Kärkkäinen; Luke Kent; et al. (European Central Bank (ECB), 2024)
In recent years, monetary policy and inflation considerations have been playing an increasingly important role for macroprudential authorities in their policy setting. This paper aims to assess the implications of high inflation and rising interest rates for macroprudential policy stance. The conceptual discussions and model-based analyses included in this paper reflect on the appropriate direction and impact of macroprudential policies at the different stages of financial and business cycles, given cross-country and banking system heterogeneities. In this context, a key objective of the paper is to assess to what extent the interaction between macroprudential and monetary policies differs, given the heterogeneity across euro area countries exposed to a homogenous monetary policy. While both policies are to a large extent complementary, monetary policy may generate relevant spillovers due to its impact on the financial cycle and, potentially, on financial stability. The paper argues that the recent focus of macroprudential policy on resilience, when banking sector conditions ensure no unwarranted procyclical effects of macroprudential tightening, suggests an expansion of the notion of "complementarity" with monetary policy. Specifically, with the build-up of resilience, macroprudential policy acts de facto countercyclically, supporting monetary policy in its pursuit of price stability. In this regard, the paper stresses that the source of the inflationary shock (supply versus demand side) and the monetary environment primarily affect the intensity, speed and extent of buffer build-up or release within each stage of the financial cycle while affecting borrower-based measures in their bindingness.
Keywords: E52; G21; G28; 330; banks; macroprudential policy; capital buffers; borrower-based measures; Financial stability; monetary policy; financial risk; bank; interest; inflation